Menjelajahi Tren Design Thinking dalam Pendidikan: Tinjauan Literatur Sistematis dari Jurnal Terindeks Web of Science dalam Desain Instruksional dan Desain Sistem Instruksional - Lardiatama, Trada; Wigati, Wigati (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The use of Design Thinking in the field of education has become a major highlight as a relevant problem solving method. Problem solving ability is one of the essential competencies in the context of 21st century education. This research uses content analysis of a number of articles contained in the Web of Science (WOS) database, with the main focus on the application of Design Thinking (DT) within the framework of Instructional Design (ID) and/or Instructional System Design (ISD). This research aims to complement the previous report, "Design Thinking in Education: Perspectives, Opportunities and Challenges" (Panke, S., 2019), which has investigated the role of DT in education. Although the number of publications specifically exploring DT in ID and ISD is still limited, research trends show a significant increase from year to year. Based on the search results, publications exploring the use of DT in ID and ISD tend to be qualitative in nature, often in the form of multiple case studies. Several publications highlight subjects and materials that aim to improve student competence, learning processes, and learning design. Despite this, publications that focus on the role of instructional designers are still relatively limited. Several recommendations have been proposed for future research, with the aim of supporting the adoption of DT by Instructional Designers as a primary focus. These findings will provide valuable insight for further developments in the use of Design Thinking in the field of Education.